Amniotic fluid discordance in monochorionic diamniotic twin pregnancies is associated with increased risk for twin anemia–polycythemia sequence. (3rd November 2016) - Hiersch, Liran; Eitan, Mayan; Ashwal, Eran; Weisz, Boaz; Chayen, Benny; Lipitz, Shlomo; Yinon, Yoav
Abstract: Objective: To estimate the risk for twin anemia–polycythemia sequence (TAPS) and adverse perinatal outcome in monochorionic diamniotic (MCDA) twin pregnancies with amniotic fluid discordance (AFD). Methods: Retrospective cohort study of 34 MCDA pregnancies with AFD (intertwin difference of ≥3 cm in maximal vertical pocket measurement) without meeting the criteria for twin to twin transfusion syndrome or selective intrauterine growth restriction. Perinatal outcome measures and the risk for TAPS were compared with a control group consisted of 101 MCDA twin pregnancies without AFD, twin to twin transfusion syndrome, or selective intrauterine growth restriction. Composite neonatal morbidity was defined as the presence of respiratory distress syndrome, intraventricular hemorrhage grades 3 and 4, necrotizing enterocolitis or sepsis. Results: Overall, in the AFD group, seven twin pairs (20.6%) were complicated by TAPS compared with none in the controls ( p  < 0.001). In the AFD group, women who developed TAPS had significantly higher AFD compared with women who did not develop TAPS (7.3 cm vs 4.2 cm, p  < 0.01). Patients in the AFD group delivered earlier (34.6 vs 35.8 weeks, p  < 0.001) and had significantly higher rate of composite neonatal morbidity compared with the control group (13.2 vs 2.5%, p  = 0.002). Conclusions: Despite the overall favorable outcome, MCDA twins with AFD are at increased risk for developing TAPS. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? The clinical significance of amniotic fluid discordance (AFD) without meeting the criteria for twin to twin transfusion syndrome (TTTS) is not clear. What does this study adds? Monochorionic diamniotic (MCDA) twin pregnancies complicated by AFD are at increased risk of early delivery as compared with uncomplicated MCDA twins. The risk for twin anemia–polycythemia sequence (TAPS) was higher among MCDA twins with AFD, and this risk appeared to be related to the severity of AFD.